Ukraine - Russia, G20 Summit, and Indonesia's Presidency Challenge - Akbar, Yonarisman Muhammad (HM Publisher, 2024)
This article describes three key issues in the global geopolitical context: the conflict between Ukraine and Russia, Indonesia's role as president of the G20 Summit, and the challenges faced in addressing both. The conflict between Ukraine and Russia has been a source of international tension since 2014, with far-reaching consequences for regional and global stability. Meanwhile, Indonesia, as president of the G20 Summit, is faced with the important task of facilitating dialogue between member states in addressing global economic issues, including the prolonged impact of the COVID-19 pandemic. Using content analysis research methods and in-depth interviews with the Ukrainian Ambassador and the Russian Ambassador, this research addresses the key challenge for Indonesia of playing an effective mediation role in the Ukraine-Russia conflict while promoting economic cooperation and global justice. The solution to this challenge requires active cooperation between G20 member states and a focus on inclusive economic recovery and sustainable peace.